Sejarah Ilmu Nahwu dan Perkembangannya - Anwar Abd. Rahman (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2010)
Almost all Arabic linguists agree that Ali bin Abi Thalib was the first' initiator and pioneer who developed Nahwu. This idea was disclosed by Ali when he was ruling the government. This idea appeared due to some factors, among others is religious factor mainly in the effort of purifying AI-Quran from lahn (misreading). This problem actually existed since the prophetic era, then continued to Khulafa al-Rasyidun. However, lahn became prime and collective awareness and attention of Bani Umayyah dinasty since most people made many mistakes in using languages, not only by grass rooted community, but also by linguists.